1966
DOI: 10.1002/1097-0142(196603)19:3<395::aid-cncr2820190313>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Colpomicroscopic studies of cervical intraepithelial neoplasia

Abstract: This paper reports colpomicroscopic observations on 750 patients with abnormal Papanicolaou smears and delineates the diagnostic criteria used in colpomicroscopy. The detection rate in a prospective series of 100 women was 84% and the diagnostic accuracy 68%. Of special interest in this study was a group of patients who had a minute area of mild dysplasia found on the squamous side of the squamo‐columnar junction. Each of these areas was unifocal and was associated with a smear in which the abnormal cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0
24

Year Published

1966
1966
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(162 citation statements)
references
References 4 publications
3
135
0
24
Order By: Relevance
“…The prevalence of CIN 3 was 0.19% (6/3088), with an age range of 35 to 51 years. If the results are compared with the literature, 14,17 they reveal that the prevalence of CIN 1 and CIN 2 is lower than in other developed countries, i.e., 1.2% vs. 2.6%, with a wider range of age population of 23-53 years in our series compared to 25-29 years in the literature. The prevalence of CIN 3 in our population was approximately 0.2%, with an age range of 35-51 years, as against 0.5% and age range of 35-39 years in the literature.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…The prevalence of CIN 3 was 0.19% (6/3088), with an age range of 35 to 51 years. If the results are compared with the literature, 14,17 they reveal that the prevalence of CIN 1 and CIN 2 is lower than in other developed countries, i.e., 1.2% vs. 2.6%, with a wider range of age population of 23-53 years in our series compared to 25-29 years in the literature. The prevalence of CIN 3 in our population was approximately 0.2%, with an age range of 35-51 years, as against 0.5% and age range of 35-39 years in the literature.…”
Section: Discussionsupporting
confidence: 43%
“…HPV subtypes 6 and 11 cause benign lesions such as flat condyloma and mild atypia, whereas HPV 16, 18 and 31, that are called "oncogenic virus," produce high-grade cytological atypia (CIN 2, 3). By using Pap smear and colposcopy without biopsy in large-scale studies of patients who had had two or three abnormal cervical smears and who were followed for nine years, Richart 14 found that 50% of women with CIN 1 progressed to CIN 3, and 16% progressed to CIN 2. The remaining 28% persisted at the same grade CIN 1 and only 6% of the patients regressed.…”
Section: Discussionmentioning
confidence: 99%
“…Five microliters of first-strand cDNA (1/10 volume of first-strand cDNA obtained from 150 ng of total RNA) were mixed with a master mix composed of 40 mM tricine-KOH (pH 9.2), 15 mM KoAc, 3.5 mM Mg(OAC) 2 , 75 g/ml BSA, 0.2 mM dNTP, 0.2 M AAG CAG TGG TAT CAA CGC AGA GT and 1 ϫ Advantage KlenTaq Polymerase mix (Clontech). cDNA was then amplified by PCR using the following program profile: denaturation at 95°C for 1 min, followed by 32 cycles of 95°C for 5 sec, 65°C for 5 sec and 68°C for 3 min.…”
Section: Cdna Amplificationmentioning
confidence: 99%
“…These are termed CIN1, CIN2 or CIN3 depending on the degree of severity. 2,3 According to a critical review of 73 studies on the natural history of CIN, the likelihood of regression of CIN1 is 60%, persistence 30%, progression to CIN3 10% and progression to invasive cancer 1%. The corresponding approximations for CIN2 are 40%, 35%, 20% and 5%.…”
mentioning
confidence: 99%
“…In the vulva and vagina, we began to report entities such as angiomyofibroblastoma (Alameda et al, 2006) and aggressive angiomyxoma (Ockner et al, 1997) with confidence (entities that confused us previously, especially in differentiating these lesions from the more common fibroepithleial polyp) by very careful observation of the histologic features. In the cervix, we initially used the CIN (Cervical Intraepithelial Neoplasia) classification of the 1970s for squamous intraepithelial lesions, but in the early 2000s, we switched to the SIL (Squamous Intraepithelial Lesion) system (Richart, 1973;National Cancer Institute Workshop, 1988;Crum, 2003). Squamous intraepithelial lesions and squamous cell carcinomas of cervix are not very common in Pakistan.…”
Section: Female Genital Tract Pathologymentioning
confidence: 99%